Very severe aplastic anemia in a child with pulmonary mucormycosis: a case report - Huang, Minchun; Jiang, Nanchuan; Ren, Yahui; Peng, Yun; Wu, Xiaoyan (Frontiers in Pediatrics, 2024)
Aplastic anemia (AA), is a rare but potentially life-threatening disease characterized by pancytopenia and a hypocellular bone marrow. Pulmonary mucormycosis (PM) is a rare but lifethreatening fungal infection observed in immunocompromised patients, particularly those with neutropenia and those using corticosteroids, with a high mortality rate from 40 to 80%. However, PM diagnosis and treatment remain challenging. This study reports a case of very severe aplastic anemia (VSAA) in a male child with PM. The innovation of this article lies in the following aspects: the patient exhibited typical clinical manifestations, the reverse halo sign (RHS) on chest computed tomography (CT), and a positive metagenomic next-generation sequencing (mNGS) analysis; despite aggressive anti-infective treatment and left lower lobectomy, he experienced a poor clinical outcome. Reflecting on cases with poor prognosis can indeed offer valuable insights and opportunities for learning. This study underlines the diagnostic challenges in mucormycosis, which should be considered in persistent fever that is unresponsive to standard antibiotic and antifungal therapies, and conduct a comprehensive examination to achieve early detection, diagnosis and treatment. It was concluded that, in addition to antifungal treatment, early surgery is essential for treating mucormycosis.